Assembly and annotation of the Gossypium barbadense L. ‘Pima-S6’ genome raise questions about the chromosome structure and gene content of Gossypium barbadense genomes - Ricardo A. Chávez Montes; Mauricio Ulloa; Tammy Biniashvili; Arik Zackay; Nir Kfir; Damar Lopez-Arredondo; Luis Herrera-Estrella (BMC Genomics, 2023)
Abstract Background Gossypium barbadense L. Pima cotton is known for its resistance to Fusarium wilt and for producing fibers of superior quality highly prized in the textile market. We report a high-quality genome assembly and annotation of Pima-S6 cotton and its comparison at the chromosome and protein level to other ten Gossypium published genome assemblies. Results Synteny and orthogroup analyses revealed important differences on chromosome structure and annotated proteins content between our Pima-S6 and other publicly available G. barbadense assemblies, and across Gossypium assemblies in general. Detailed synteny analyses revealed chromosomal rearrangements between Pima-S6 and other Pima genomes on several chromosomes, with three major inversions in chromosomes A09, A13 and D05, raising questions about the true chromosome structure of Gossypium barbadense genomes. Conclusion Analyses of the re-assembled and re-annotated genome of the close relative G. barbadense Pima 3–79 using our Pima-S6 assembly suggest that contig placement of some recent G. barbadense assemblies might have been unduly influenced by the use of the G. hirsutum TM-1 genome as the anchoring reference. The Pima-S6 reference genome provides a valuable genomic resource and offers new insights on genomic structure, and can serve as G. barbadense genome reference for future assemblies and further support FOV4-related studies and breeding efforts.